2019
DOI: 10.2147/imcrj.s212848
|View full text |Cite
|
Sign up to set email alerts
|

<p>Acute hypervitaminosis A misdiagnosed as malaria in a 7-year-old Nigerian boy</p>

Abstract: Vitamin A supplementation program where single high-dose vitamin A supplements are provided to the qualified (infants and children) at regular intervals is operational in Nigeria as a public health initiative to control vitamin A deficiency which is prevalent in our country in accordance with the WHO recommendations. Reports of symptomatic acute hypervitaminosis A are scarce. We report a case of acute hypervitaminosis A resulting from accidental ingestion of vitamin A supplement capsules. This is to reiterate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The result of the present study showed the exposure of adult female mice to the RA (25 and 50 mg) caused suppression in their activities and decreases of food intake, these observations are in agreement with the result of Aguwa et al, (2016), Their results revealed that when the rats were exposed to an overdose (400 and 500mg/kg) of vitamin A for 14 days resulted in general body fatigue, decreased food and water uptake and the rats become smaller, shrunk, weak, and waif. The loss of appetite is a symptom seen in many case reports of hypervitaminosis A and during the administration of medication analogs to vitamin A metabolites (NIH, 2017;Vallerand et al, 2018;Babatola et al, 2019). Another effect of RA was the loss of hair (fur) around the mouth, this finding is in agreement with Okano et al, (2012), this report demonstrated that hair loss is associated with excess administration of RA.…”
Section: Discussionsupporting
confidence: 75%
“…The result of the present study showed the exposure of adult female mice to the RA (25 and 50 mg) caused suppression in their activities and decreases of food intake, these observations are in agreement with the result of Aguwa et al, (2016), Their results revealed that when the rats were exposed to an overdose (400 and 500mg/kg) of vitamin A for 14 days resulted in general body fatigue, decreased food and water uptake and the rats become smaller, shrunk, weak, and waif. The loss of appetite is a symptom seen in many case reports of hypervitaminosis A and during the administration of medication analogs to vitamin A metabolites (NIH, 2017;Vallerand et al, 2018;Babatola et al, 2019). Another effect of RA was the loss of hair (fur) around the mouth, this finding is in agreement with Okano et al, (2012), this report demonstrated that hair loss is associated with excess administration of RA.…”
Section: Discussionsupporting
confidence: 75%
“…In another part of the country, a study evaluated 2,171 records of patients managed for uncomplicated malaria and found that only 480 had laboratory confirmation of malaria and the rest were given presumptive diagnosis of malaria and subsequently treated, with no laboratory evidence [ 19 ]. More recently, hypervitaminosis A was misdiagnosed as malaria in a 7-year-old boy who presented with vomiting, headache, generalized body weakness, and blurred vision [ 20 ]. Despite WHO´s guideline requiring laboratory confirmation of malaria diagnosis prior to treatment, there are overwhelming cases of presumptive diagnosis by clinicians, caregivers, and patent medicine dealers.…”
Section: Essaymentioning
confidence: 99%